Case Report: Potential of pharmacological treatment for auditory abnormal sensations with aripiprazole: a report of two cases - Goto, Fumiyuki; Kaneda, Shoji; Okami, Kenji; Wasano, Koichiro (Frontiers in Psychiatry, 2025)
Auditory abnormal sensations encompass various subjective auditory symptoms such as tinnitus, hyperacusis, aural fullness, autophony, dysacusis, pseudo-hallucinations, and misophonia. Although tinnitus management typically includes lifestyle counseling and sound therapy, there remains no established treatment for symptoms like aural fullness or pseudo-hallucinations with unknown etiology. In cases where central sensory processing abnormalities or emotional instability are suspected, psychotropic medications may offer benefit. We report two cases in which aripiprazole, an atypical antipsychotic, was effective in treating such symptoms. In both cases, traditional approaches such as antidepressants and supportive therapy were insufficient, but aripiprazole led to marked improvement in subjective auditory symptoms. These cases suggest a potential role for pharmacological modulation of central sensory and emotional regulation in patients with auditory abnormal sensations. One involved a man with phonophobia and aural fullness, and the other a woman with tinnitus and pseudo-hallucinations.